Analysis of the impact of the Xiaolangdi Reservoir on the runoff of the Yellow River downstream based on CEEMDAN-multiscale information entropy - Xianqi Zhang; Wenbao Qiao; Jiafeng Huang; Jingwen Shi; Minghui Zhang (Water Science and Technology, 2023)
Water resources are vital to the development of human society, and mastering the law of runoff changes is the basis for achieving sustainable use of water resources. To study the impact of reservoir construction on the changes of downstream river runoff, this paper decomposes the runoff before and after reservoir construction using the CEEMDAN method based on the runoff data from the Huayuankou hydrological station. The fluctuation characteristics of each decomposition series of runoff before and after reservoir construction and the intra-annual variation pattern of runoff are also analyzed by combining multi-time information entropy and coefficient of variation. The results show that after the operation of the Xiaolangdi Reservoir, the annual runoff variation cycle tends to be flat, and the monthly runoff cycle is significantly reduced. After reservoir construction, the entropy values of each IMF and Res of runoff become larger, the complexity and randomness of runoff changes increase, and predictability decreases. Before and after the operation of the Xiaolangdi Reservoir, the coefficient of variation of runoff were 0.28–1 and 0.38–0.83, the distribution of runoff was more uniform, and the percentage of runoff in the flood season was reduced from 51.51 to 39.89%. HIGHLIGHTS Analysis of runoff data using CEEMDAN and multiscale information entropy.; Analysis from several perspectives, including inter- and intra-year perspectives.; Analysis of monthly runoff using dispersion coefficients and monthly runoff process lines.; The influence of the reservoir on the runoff of the lower Yellow River was studied.;